2001
DOI: 10.1007/pl00004100
|View full text |Cite
|
Sign up to set email alerts
|

Utility and entropy

Abstract: In this paper we study an astonishing similarity between the utility representation problem in economics and the entropy representation problem in thermodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 10 publications
0
58
0
Order By: Relevance
“…Utility in economics has been formulated as a potential function, meaning that the equivalence classes of the ordinal relation provide a so-called foliation of the space of consumption profiles (a set of noncrossing "leaves" that fill the consumption space), or more stringently, that the difference in the cardinal utility between any two profiles can be computed as the sum of utility differences along any path in the consumption space connecting the two profiles. The existence of a utility representation of preferences is a notorious problem in economics [27,28], and in most cases where utilities can be said to exist, it is probably best to regard them as a parametric description of habitual behavior over short times, conditioned by past experience in a technological and cultural setting. 3 It is conventional in general equilibrium modeling to write goods or services directly as arguments to utility function, as if goods "have" intrinsic utility to a given agent.…”
Section: Strategy Sets and Utilitarian Valuationmentioning
confidence: 99%
“…Utility in economics has been formulated as a potential function, meaning that the equivalence classes of the ordinal relation provide a so-called foliation of the space of consumption profiles (a set of noncrossing "leaves" that fill the consumption space), or more stringently, that the difference in the cardinal utility between any two profiles can be computed as the sum of utility differences along any path in the consumption space connecting the two profiles. The existence of a utility representation of preferences is a notorious problem in economics [27,28], and in most cases where utilities can be said to exist, it is probably best to regard them as a parametric description of habitual behavior over short times, conditioned by past experience in a technological and cultural setting. 3 It is conventional in general equilibrium modeling to write goods or services directly as arguments to utility function, as if goods "have" intrinsic utility to a given agent.…”
Section: Strategy Sets and Utilitarian Valuationmentioning
confidence: 99%
“…Candeal et al [75] found a striking similarity between the utility functions in economics and the entropy in thermodynamics. Abbas et al [76] developed an optimal algorithm to obtain Von Neumann-Morgenstern utility value choice.…”
Section: Applications Of Entropy In Other Fields Of Financementioning
confidence: 95%
“…(19) A rational person would choose the expected value of |y with an observableX EU(|y ) = y|X|y (20) and since…”
Section: The Derivation Of Probabilities For Real Amplitudesmentioning
confidence: 99%
“…That the rewards are determined by the negative information content is already known and is used for the utility representation problems in economics [20][21][22] …”
Section: H(a) : = Eu(a)mentioning
confidence: 99%